THE COMPARISON OF THE IMPERFECT JAVANESE LANGUAGE ABILITY IN THE 10 – 11 YEARS OLD BOYS AND GIRLS IN KENDAL CENTRAL JAVA - Dr. Sunarya M.Hum. (Universitas PGRI Semarang, 2021)
The use of Javanese language by 10 - 11 years old children in Kendal Central Java experienced some imperfection especially from the diction, grammatical, and semantic aspects. This research took the sample from 5th grade children in SDN 3 Kutoarjo, Kendal Central Java. This research used qualititave method by describing the language aspects which were resulted by the 5th grade children in oral story by using pictorial media. The analytical technique in use was direct method which was the direct analysis on language aspects such as vocabularies, grammatical, and its meaning. The data collection was collected by recording, listening, and taking note in order to collect the representative data. According to some analysis , it could be known that in javanese language ability by the 10 to 11 years old children frequently did the imperfection, especially in vocabulary, grammatical, and meaning aspects.